(untitled) (Research, Society and Development, 2021)
Fluoroquinolones are synthetic drugs that have evolved over time, being formed by a group of antibiotics developed from nalidixic acid, thus containing four generations with structural differences that alter the spectrum of activity. Fluroquinolones are used worldwide in the treatment of infections of bacterial origin. This study aimed to gather information on the use of fluoroquinolones in domestic dogs and cats. To conduct this literature review, data were collected from 2006 to 2019 in the literature available at the Capes Portal, Google Scholar and books, using the following descriptors: fluroquinolones in dogs and fluroquinolones in cats, also using these words in Portuguese. From this search it can be seen that fluroquinolones are indicated in human and veterinary therapies, and currently have very satisfactory antimicrobial activity, good availability through the oral route, good diffusion to tissues, prolonged half-life, and significantly reduced toxicity. Resistance to this antibiotic can be attributed to factors such as: indiscriminate and abusive use, ease of access, misuse in non-infectious treatments, among other factors. They are indicated mainly for dogs and cats with bacterial infections of Gram-negative, Gram-positive, and anaerobic bacteria. It is concluded that antimicrobials from the quinolone group have evolved over time with the intention of creating effective antimicrobials with broad action, minimal adverse effects, and affordability.